Evaluation and comparison of nephroprotective effect of Hemidesmus indicus Linn. and Withania somnifera Linn. on gentamicin induced nephrotoxicity in Albino rats - Padhye, Mugdha Rajeeva; Devrao Jogdand, Sangita; Bhattacharjee, Jagruti (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Nephrotoxicity is a known deleterious effect of Aminoglycoside antibiotics. This class of antibiotics is used very frequently. It is well known that Gentamicin causes renal tubular necrosis in the proximal tubular cells. Phytochemicals are being studied extensively and have proved to be of benefit in various diseases. The use of phytochemicals would minimize the adverse effects encountered with these antibiotics. Comparison between various phytochemicals would help in optimizing dosage and duration of treatment. In the present study we studied and compared the nephroprotective effect of Hemidesmus Indicus Linn. and Withania Somnifera Linn. on Gentamicin induced nephrotoxicity in Albino rats. Methods: Wistar albino rats weighing 180-250Gms were utilized for the present study. The root extract of these Hemidesmus Indicus Linn. and Withania Somnifera Linn. was administered orally to rats for 10 days concurrently with Gentamicin. Nephrotoxicty was assessed following a single dose injection of Gentamicin. Nephroprotective effect was assessed after 10 days of administering Hemidesmus Indicus Linn. and Withania Somnifera Linn. Renal function was assessed using Blood Urea, Serum Creatinie, SOD (Superoxide Dismutase) and MDA (Malondialdehyde) as parameters. Results: Statistically significant improvement in renal function (p <0.05) was seen after administration of Hemidesmus Indicus and Withania Somnifera in Gentamicin treated rats. There was significant reduction in blood urea, serum creatinine and MDA levels with an increase in SOD levels. Conclusions: Withania Somnifera and Hemidesmus Indicus had nephroprotective effect. However, Withania Somnifera was found to be more nphroprotective than Hemidesmus Indicus.